Impact of External Governance Mechanism on the Performance of Listed Banks of Pakistan with the Moderating Role of Government Ownership - Ali, Shoaib; Naveed, Hafiz Muhammad (Quantitative Economics and Management Studies, 2020)
This research aims to examine the external governance process boosts the performance of Pakistan's listed commercial banks by estimating the return on equity (ROE) and earnings per share (EPS). The research involved external governance mechanism with the moderating role of government ownership. The study's sample structure consists of Pakistan Stock Exchange (PSX) listed banks with the existence of government ownership from 2014 to 2018. Data is obtained as well from financial statements, shareholding trends, and the Credit Rating Agency of Pakistan (PACRA). To meet the specific aim of the research and to satisfy the goals of the analysis, the panel data methodology (fixed effect and random effect model) has been applied. The findings have shown that the external governance system plays an important role in the banking sector's accountability and performance. Government ownership may also improve banking institution efficiency by improving external governance mechanisms. This study will allow commercial banks to overcome the challenges and boost efficiency with the external governance mechanism and devise better working strategies. This study makes it easier for the bankers' rulers to run the external governance system to strengthen bank efficiency. This work is unique because no one defined an external governance system with government ownership as a moderating role.